Enhancing Students Sustainability Understanding Through Air Quality Monitor Project Using Arduino - Faizah, Zahra; Widodo, Ari; Eliyawati*, Eliyawati (Universitas Syiah Kuala, 2024)
As an environmental degradation, air pollution is contrary to sustainable development goals (SDGs). Therefore, through education for sustainable development (ESD), there is a need to enhance students capability in solving such problem. STEM learning encourages students to work on real-world problem through hands on activity in line with ESD necessity. This research aims to analyze how the ESD-based STEM learning practice through air quality monitor project using Arduino could influence students sustainability understanding in solving air pollution. Students sustainability understanding towards air pollution which was measured is based on cognitive learning objectives related to SDGs number 3 good health and well-being, SDGs 7 affordable and clean energy, SDGs 12 responsible consumption and production, SDGs 13 Climate action, and SDGs 15 Life on land. The research uses quasi experimental method with pretest-posttest design. This research also developed the instrument to measure sustainability understanding about air pollution. The result of data analysis shows that after the treatment, there is no significant difference between control and experiment class in students sustainability understanding. The result implies that the activity of making air quality monitor does not give significant difference in enhancing sustainability understanding. However, the result migh be influenced by some factors which make the implementation of ESD-based STEM learning to be not optimal